PPC-based TPU material with high tensile strength and light stability and preparation thereof
By introducing a linear light stabilizer into the TPU material, the problems of tensile strength and yellowing of the TPU material are solved, the combination of high tensile strength and light stability is achieved, the preparation process is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202510803063.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-09-26
AI Technical Summary
Existing TPU materials have problems with low tensile strength and easy yellowing, especially under ultraviolet light, which affects the material's light transmittance and aesthetics. At the same time, the traditional method of adding light stabilizers is complex and costly, and the effect is unstable.
PPC, diphenylmethane diisocyanate and 1,4-butanediol are used as raw materials, a linear light stabilizer is added as an additive, and they are blended and extruded under the action of a catalyst to prepare a high tensile strength, light-stable PPC-based TPU material. The light stabilizer directly participates in the raw material reaction and is blocked in the hard segment.
The tensile strength and UV resistance of TPU materials are improved, the light stabilizer is not easy to migrate, the operation is simple, the cost is low, and it is suitable for industrial promotion.
Smart Images

Figure BDA0005451840550000032 
Figure BDA0005451840550000034 
Figure BDA0005451840550000042
Abstract
Description
Technical Field
[0001] The present invention relates to a TPU material and its preparation, in particular to a high-tensile-strength, light-stable PPC-based TPU material and its preparation. Background Art
[0002] TPU, also known as thermoplastic polyurethane elastomer or thermoplastic polyurethane rubber, is a (AB)n-type segmented linear polymer, where A is a high molecular weight (1000-6000) polyester or polyether, B is a diol with 2-12 linear carbon atoms, and the chemical structure between the A and B segments is a diisocyanate. It is heat-plasticizable and solvent-soluble, and exhibits excellent overall properties such as high strength, high toughness, wear resistance, and oil resistance. It also has good processability and is widely used in industries such as defense, medical care, and food.
[0003] PPC, a polypropylene carbonate material, boasts advantages such as biodegradability, non-toxicity, and environmental friendliness, and has a wide range of applications in the field of polymer materials. For example, Wu et al., in their comparative analysis of the performance of thermoplastic polyurethane and biodegradable polyurethane-polypropylene carbonate, noted that combining TPU with PPC to create a TPU-PPC composite material exhibits improved physical and mechanical properties, water resistance, chemical stability, and biodegradability. However, the TPU-PPC composite material described in this article is prepared by blending PPC with a finished TPU product, rather than directly using PPC as the raw material to prepare the TPU material.
[0004] Patent publication number CN102838717A discloses a process for preparing thermoplastic polyurethane elastomers using polypropylene carbonate as a soft segment. Specifically, the process involves first adding a diisocyanate and a catalyst to a polypropylene carbonate polyol for reaction, then adding a chain extender for chain extension, and drying and curing to obtain a thermoplastic polyurethane elastomer. This invention features a simple process, abundant raw material sources, and low production costs. The thermoplastic polyurethane elastomer is prepared using a prepolymerization method, exhibiting strong plasticity and excellent performance, and the elastomer's tensile properties can be adjusted at will. The main drawback of the material disclosed in this patent is that, while it possesses excellent plasticity and elongation at break, its tensile strength is low, which cannot meet the industry application requirements for products requiring high tensile strength.
[0005] In addition, many types of polyurethane materials often suffer from yellowing. After absorbing light with a wavelength greater than 340nm, unstable peroxides are easily formed in the material, which in turn forms a chromophore monoquinone imide structure, causing the polyurethane to yellow. Further oxidation generates a diquinone imide structure, ultimately turning it amber. Alternatively, after absorbing light with a wavelength less than 340nm, polyurethane undergoes a Photo-Fries rearrangement, forming aromatic amines, which further degrade and cause yellowing. TPU materials contain benzene ring structures, which are easily affected by ultraviolet light and cause yellowing, significantly affecting light transmittance and aesthetics.
[0006] In order to overcome the yellowing defect, light stabilizers are usually added to current polyurethane materials for improvement. However, the traditional method of adding light stabilizers is physical blending with the polyurethane material. This method requires secondary operations, is cumbersome to process, and is costly. In addition, small molecule light stabilizers may migrate during use, thereby reducing the light stabilization effect, causing yellowing and affecting the appearance of the product.
[0007] Therefore, how to solve the yellowing problem of TPU materials and the poor mechanical properties of PPC-based TPU with simpler processes and lower costs is one of the current hot research directions in the field of polyurethane materials. Summary of the Invention
[0008] To address the above technical problems, the present invention provides a high-tensile-strength, light-stable PPC-based TPU material and its preparation. The PCC-based TPU material of the present invention has high tensile strength, strong UV resistance, good light stability, and is not prone to yellowing. Furthermore, the present invention has a simple process and low cost, making it suitable for industrial promotion and application.
[0009] One of the technical solutions of the present invention:
[0010] Provided is a high tensile strength, light-stable PPC-based TPU material, the general chemical structure of which is shown in Formula I or Formula II:
[0011] Formula I:
[0012] Formula II:
[0013] Among them, a:b:c=1:3:0.01-0.03;
[0014] R1 is: n is a positive integer from 10 to 40; R2 is: N-R3-N is one of the following structures:
[0015]
[0016] n is an integer from 2 to 20;
[0017]
[0018] O-R3-O is:
[0019] The second technical solution of the present invention:
[0020] Provided is a preparation method for a high-tensile-strength, light-stable PPC-based TPU material, which is obtained by blending and extruding PPC, diphenylmethane diisocyanate, and 1,4-butanediol as raw materials and a linear light stabilizer as an additive under the action of a catalyst.
[0021] Preferably, the preparation process of the aforementioned high tensile strength, light-stable PPC-based TPU material comprises the following steps:
[0022] (1) taking the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst in proportion, drying and mixing them for later use;
[0023] (2) adding the mixture of step (1) into a twin-screw extruder and extruding to obtain an extrudate;
[0024] (3) Curing the extrudate of step (2) to obtain the TPU material.
[0025] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the linear light stabilizer is one of the following structures:
[0026] n is an integer from 2 to 20,
[0027]
[0028] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the catalyst is stannous octoate or dibutyltin dilaurate.
[0029] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the mass ratio of the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst is 100:40-60:8-18:0.1-1:0.1-0.6.
[0030] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the mass ratio of PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst is 100:45-55:10-15:0.3-0.7:0.2-0.4.
[0031] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the mass ratio of the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst is 100:49.19:13.08:0.48:0.32.
[0032] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the extrusion temperature of the twin-screw extruder is 140-200°C.
[0033] Preferably, in the preparation of the aforementioned high tensile strength, light-stable PPC-based TPU material, the aging temperature is 70-90° C., and the aging time is 20-30 hours.
[0034] Beneficial effects of the present invention:
[0035] 1. The TPU material of the present invention is prepared with PPC as raw material and has many advantages such as biodegradability. In addition, by introducing a linear light stabilizer into the TPU material and making it part of the hard segment, the tensile strength of the PPC-based TPU material is improved, and the mechanical properties are better.
[0036] 2. The introduction of a linear light stabilizer into the TPU material of the present invention makes it UV-resistant and has the advantage of being less prone to yellowing.
[0037] 3. The light stabilizer of the present invention directly participates in the raw material reaction and is blocked in the hard segment. Compared with the method of adding the light stabilizer later, the light stabilizer in the TPU material of the present invention is not easy to migrate and has better stability.
[0038] 4. The light stabilizer of the present invention directly participates in the raw material reaction during the preparation of TPU materials, without the need for secondary processing, making the operation simpler and more suitable for industrial promotion. DETAILED DESCRIPTION
[0039] The present invention will be further described below with reference to the examples, but they are not intended to limit the present invention.
[0040] Embodiments of the Invention
[0041] The chemical structural formulas of the raw materials used in the comparative examples and embodiments of the present invention are as follows:
[0042] PPC: Abbreviated as HO-R1-OH;
[0043] MDI: Abbreviated as OCN-R2-NCO;
[0044] The abbreviation of linear light stabilizer is: HN-R3-NH or HO-R3-OH.
[0045] The reaction formula of the TPU material of the embodiment of the present invention is as follows:
[0046] (1)
[0047] (2)
[0048] Comparative Example 1:
[0049] PPC, 1,4-butanediol (BDO) and MDI are used as raw materials, stannous octoate (T9) is used as catalyst, and the components are mixed in a mass ratio of PPC:BDO:MDI:T9=100:13.08:48.93:0.32;
[0050] The components were mixed in proportion and dried, then added to the twin-screw reaction extruder and extruded at 160°C.
[0051] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0052] Example 1:
[0053]
[0054] PPC, 1,4-butanediol (BDO), MDI, and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (LS1) were used as raw materials, and stannous octoate (T9) was used as a catalyst. The molar ratio of the soft and hard segments was 1:3. The R value was 1.01. The catalyst equivalent was 0.2%. The LS1 dosage was 0.3% of the total mass. The components were formulated in the mass ratio of PPC:BDO:MDI:LS1:T9 = 100:13.08:49.19:0.48:0.32.
[0055] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0056] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0057] Example 2:
[0058]
[0059] PPC, 1,4-butanediol (BDO), and MDI were used as raw materials, bis(2,2,6,6-tetramethyl-4-piperidinyl) glutarate (LS2) was used as an additive, and stannous octoate (T9) was used as a catalyst. The components were mixed in a mass ratio of PPC:BDO:MDI:LS2:T9 = 100:13.08:49.23:0.49:0.32.
[0060] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0061] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0062] Example 3:
[0063]
[0064] PPC, 1,4-butanediol (BDO), and MDI were used as raw materials, bis(2,2,6,6-tetramethyl-4-piperidyl)succinate (LS3) was used as an additive, and stannous octoate (T9) was used as a catalyst. The components were mixed in a mass ratio of PPC:BDO:MDI:LS3:T9 = 100:13.08:49.43:0.50:0.32.
[0065] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0066] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0067] Example 4:
[0068]
[0069] PPC, 1,4-butanediol (BDO), and MDI were used as raw materials, bis(2,2,6,6-tetramethyl-4-piperidyl)-1,4-cyclohexanedicarboxylate (LS4) was used as an additive, and stannous octoate (T9) was used as a catalyst. The components were mixed in a mass ratio of PPC:BDO:MDI:LS4:T9=100:13.08:49.15:0.48:0.32.
[0070] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0071] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0072] Example 5:
[0073]
[0074] PPC, 1,4-butanediol (BDO), and MDI were used as raw materials, 1,4-bis(1,3,3-trimethyl-2-azabicyclo[2.2.2]oct-5-yl) succinate (LS5) was used as an additive, and stannous octoate (T9) was used as a catalyst. The components were mixed in a mass ratio of PPC:BDO:MDI:LS5:T9 = 100:13.08:49.20:0.49:0.32.
[0075] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0076] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0077] Example 6:
[0078]
[0079] PPC, 1,4-butanediol (BDO), and MDI were used as raw materials, 1,4-bis(2,6-diethyl-2,3,6-trimethyl-4-piperidinyl) succinate (LS6) was used as an additive, and stannous octoate (T9) was used as a catalyst. The components were mixed in a mass ratio of PPC:BDO:MDI:LS6:T9 = 100:13.08:49.19:0.48:0.32.
[0080] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0081] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0082] Example 7:
[0083]
[0084] PPC, 1,4-butanediol (BDO), and MDI were used as raw materials, 1,4-bis[1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinyl] succinate (LS7) was used as an additive, and stannous octoate (T9) was used as a catalyst. The components were mixed in a mass ratio of PPC:BDO:MDI:LS7:T9 = 100:13.08:49.19:0.48:0.32.
[0085] Mix the components in proportion and dry them, then add them into the twin-screw reaction extruder, set the temperature to 160℃ and extrude;
[0086] After the extruded product was aged at 80°C for 24 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0087] Example 8:
[0088] This embodiment is consistent with embodiment 1, except that a:b:c=1:3:0.01. The mass ratio of each component can be calculated as follows:
[0089] PPC: BDO: MDI: LS1: T9 = 100: 13.52: 50.68: 0.24: 0.32;
[0090] The temperature of the twin-screw reactive extruder was 140°C;
[0091] After the extruded product was aged at 70°C for 30 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0092] Example 9:
[0093] This embodiment is consistent with embodiment 1, except that a:b:c=1:3:0.02. The mass ratio of each component can be calculated as follows:
[0094] PPC: BDO: MDI: LS1: T9 = 100: 13.52: 50.8: 0.48: 0.33;
[0095] The temperature of the twin-screw reactive extruder was 150°C;
[0096] After the extruded product was aged at 75°C for 28 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0097] Example 10:
[0098] This embodiment is consistent with embodiment 1, except that a:b:c=1:3:0.03. The mass ratio of each component can be calculated as follows:
[0099] PPC: BDO: MDI: LS1: T9 = 100: 13.52: 50.96: 0.72: 0.34;
[0100] The temperature of the twin-screw reactive extruder was 200 °C;
[0101] After the extruded product was aged at 90°C for 20 hours, it was injection molded and aged in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0102] Example 11:
[0103] This embodiment is consistent with embodiment 1, except that the catalyst equivalent is 0.4%.
[0104] PPC: BDO: MDI: LS1: T9 = 100: 18: 60: 1: 0.64;
[0105] The temperature of the twin-screw reactive extruder was 180°C;
[0106] After the extruded product was aged at 85°C for 22 hours, it was injection molded and sampled. The sample was aged by UV radiation in a UV aging box. Samples with aging times of 0 hours, 50 hours, 100 hours, 150 hours, and 200 hours were taken for tensile testing.
[0107] The mechanical properties test results of Comparative Example 1 and Examples 1-11 of the present invention are shown in Table 1 below
[0108] Table 1
[0109]
[0110]
[0111] As can be seen from the table above, the addition of a reactive light stabilizer reduces the regularity of the PPC-TPU molecular chains compared to the unstabilized version. This is reflected in the macroscopic product as a decrease in tensile strength and elongation at break. After UV aging, the tensile strength and elongation at break of the comparative PPC-TPU without a light stabilizer are significantly reduced. In contrast, the performance of the PPC-TPU in the example with the addition of a reactive light stabilizer exhibits a more gradual decline. Considering both performance and cost, Examples 2 and 3 are the preferred options.
[0112] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the scope of protection of the present invention.
Claims
1. A high tensile strength, light-stable PPC-based TPU material, characterized in that: Its general chemical structure is shown in Formula I or Formula II: Formula I: Formula II: Among them, a:b:c=1:3:0.01-0.03; R1 is: n is a positive integer from 10 to 40; R2 is: N-R3-N is one of the following structures: n is an integer from 2 to 20; O-R3-O is:
2. A preparation method of the high tensile strength, light-stable PPC-based TPU material according to claim 1, characterized in that: It is obtained by mixing and extruding PPC, diphenylmethane diisocyanate and 1,4-butanediol as raw materials and a linear light stabilizer as an additive under the action of a catalyst.
3. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 2, characterized in that: The preparation process includes the following steps: (1) taking the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst in proportion, drying and mixing them for later use; (2) adding the mixture of step (1) into a twin-screw extruder and extruding to obtain an extrudate; (3) Curing the extrudate of step (2) to obtain the TPU material.
4. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 2 or 3, characterized in that: The linear light stabilizer is one of the following structures: n is an integer from 2 to 20, 5. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 2 or 3, characterized in that: The catalyst is stannous octoate and dibutyltin dilaurate.
6. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 3, characterized in that: The mass ratio of the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst is 100:49.15-60:13.08-18:0.24-1:0.32-0.
64.
7. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 6, characterized in that: The mass ratio of the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst is 100: 49.15-50.96: 13.08-13.52: 0.33-0.72: 0.32-0.
34.
8. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 7, characterized in that: The mass ratio of the PPC, diphenylmethane diisocyanate, 1,4-butanediol, additives and catalyst is 100:49.23:13.08:0.49:0.
32.
9. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 3, characterized in that: The extrusion temperature of the twin-screw extruder is 140-200°C.
10. The preparation of the high tensile strength, light-stable PPC-based TPU material according to claim 3, characterized in that: The aging temperature is 70-90° C., and the aging time is 20-30 hours.
Citation Information
Patent Citations
Preparation of thermoplastic polyurethane elastomer with polypropylene carbonate as soft segment
CN102838717A